Temporal Gene Expression Signature of Plasma Extracellular Vesicles-Micrornas from Post-Smolt Coho Salmon Challenged with Piscirickettsia Salmonis - Vidal-Soto, R (Springer, 2021)
Piscirickettsiosis is the most important bacterial disease in the Chilean salmon industry, which has borne major economic losses due to failure to control it. Cells use extracellular vesicles (EVs) as an inter-cellular communicators to deliver several factors (e.g., microRNAs) that may regulate the responses of other cells. However, there is limited knowledge about the identification and characterization of EV-miRNAs in salmonids or the effect of infections on these. In this study, Illumina sequencing technology was used to identify Coho salmon plasma EV-miRNAs upon Piscirickettsia salmonis infection at four different time points. A total of 118 novels and 188 known EV-miRNAs, including key immune teleost miRNAs families (e.g., miR-146, miR-122), were identified. A total of 245 EV-miRNAs were detected as differentially expressed (FDR < 5%) in terms of control, with a clear down-regulation pattern throughout the disease. KEGG enrichment results of EV-miRNAs target genes showed that they were grouped mainly in cellular, stress, inflammation and immune responses. Therefore, it is hypothesized that P. salmonis could potentially benefit from unbalanced modulation response of Coho salmon EV-miRNAs in order to promote a hyper-inflammatory and compromised immune response through the suppression of different key immune host miRNAs during the course of the infection, as indicated by the results of this study. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.